2012
DOI: 10.1002/aoc.2933
|View full text |Cite
|
Sign up to set email alerts
|

Efficient alkyne homocoupling catalysed by copper immobilized on functionalized silica

Abstract: Copper immobilized on a functionalized silica support is a good catalyst for the homocoupling of terminal alkynes. The so-called Glaser-Hay coupling reaction can be run in air with catalytic amounts of base. The copper catalyst is active for multiple substituted alkynes, in both polar and non-polar solvents, with good to excellent yields (75-95%). Depending on the alkyne, full conversion can be achieved within 3-24 h. The catalyst was characterized by TGA, inductively coupled plasma and X-ray photoelectron spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…8 With respect to catalysis by metals, Van Gelderen et al showed that silica-4 supported Cu was effective 9 as were ligand-stabilized Cu clusters. 10 Most recently, Boronat et al…”
Section: Introductionmentioning
confidence: 99%
“…8 With respect to catalysis by metals, Van Gelderen et al showed that silica-4 supported Cu was effective 9 as were ligand-stabilized Cu clusters. 10 Most recently, Boronat et al…”
Section: Introductionmentioning
confidence: 99%
“…In order to show the merits and limitations of the present work in comparison with other reported catalytic systems in the literatures, we summarized some of results for the synthesis of 1,2‐diphenylethyne via homo‐coupling of phenylacetylene in Table . As can be seen in this table, the present catalytic system is an equally or more efficient to those previously reported in this reaction, since the use of precious metal catalyst, [12, 15,] high reaction temperature, or the employment of unrecyclable catalysts can be avoided.…”
Section: Resultsmentioning
confidence: 58%
“…Various catalytic systems have been developed for this reaction using O 2 or air as the oxidant, including the use of Cu, Pd, Ag, Au and bimetallic Pd/Cu, Pd/Ag and Fe/Cu . Some heterogeneous catalysts, like silica/chitosan core–shell hybrid‐microsphere‐supported CuI, copper nanoparticles supported on silica coated maghemite, copper immobilized on functionalized silica, polymer‐supported copper, Cu(I) immobilized on functionalized SBA‐15, immobilized copper in MCM‐41, mesoporous silica‐supported copper, copper immobilized on nano‐silica triazine dendrimer, copper‐impregnated magnetite have also been successfully employed to promote this reaction. In 2016, Sheng et al reported that copper porphyrin acted as an efficient catalyst with high TON .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the uses of copper FS catalysts in coupling reactions are widespread. Copper(I) FS catalysts are efficiently utilized in A 3 coupling, Glaser‐Hay coupling and Sonogashira coupling reactions . Furthermore, copper(0) FS and copper(II) FS are the efficient catalysts in A 3 coupling and C−N coupling reactions, respectively.…”
Section: Applications and Advantages Of Fs‐based Catalystsmentioning
confidence: 99%